Nepal : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Nepal has grappled with formidable economic and social challenges. Although the Nepalese economy performed well, growth has been hampered by weak infrastructure, low saving and investment rates, fiscal constraints, and a lack of absorptive capacity for boosting the needed public investment. Fiscal performance has been favorable, but progress in the area of structural reform was less encouraging. The report analyzes the recent macroeconomic developments, poverty, and environmental issues. The study also reviews the country's external and monetary developments, the fiscal situation, and structural issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet